First-Episode Patients Report Cognitive Difficulties in Executive Functioning 1 Year After Initial Episode of Major Depressive Disorder - Schmid, Marit; Hammar, Åsa (Frontiers in Psychiatry, 2021)
Objective: Major Depressive Disorder (MDD) is associated with cognitive impairment in general, and Executive Functioning (EF) in particular, even in remitted phase of the disorder, suggesting residual cognitive symptoms. The aim of the present study was to investigate self-reported EF one year after the first episode of MDD and to explore this in relation to depressive mood symptoms, remission and relapse. Method: The study included data from 24 patients and 23 healthy control subjects one year after the patients’ initial first episode of MDD. All participants completed the Behavior Rating Inventory of Executive Functioning-Adult version (BRIEF-A), a standardized self-report measure of perceived EF in everyday life, measuring nine different EF. Total index scores for metacognitive functions, behaviour/emotional regulation functions and a global EF score is also calculated. Results: The patient group in total, independent of symptom status, reported significantly lower EF in all indexes compared to the healthy controls one year after the initial episode. However, higher depressive mood symptom load correlated with self-reported difficulties in metacognitive functions and poor global EF scores. Regulatory control of behaviour and emotional responses did not correlate with mood symptoms, but low self-report scores on this measure was associated with relapse during the first year after the initial episode. Conclusion: First-episode patients report significant lower executive functioning in everyday life compared to individually matched healthy controls, one year after onset, independent of symptom load. Residual cognitive symptoms seem to be evident and associated with risk of relapse and should be targeted in treatment and prevention of recurrence in MDD.